VD_FINDINFO Jug / 2015 / 381 vom 12. Oktober 2015 - VD Tribunal cantonal (2015)
PRESTATION DE LIBRE PASSAGE, DIVORCE, PARTAGESENS GÉNÉRAL, PRÉVOYANCE PROFESSIONNELLE, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 CC, 22 LFLP, 15 al. 2 LPP, 7 OLP, 8a al. 1 OLP, 12 OPP2